2016
DOI: 10.1038/srep21596
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific protease 4 controls metastatic potential through β-catenin stabilization in brain metastatic lung adenocarcinoma

Abstract: Brain metastasis is the most common type of intracranial cancer and is the main cause of cancer-associated mortality. Brain metastasis mainly originates from lung cancer. Using a previously established in vitro brain metastatic model, we found that brain metastatic PC14PE6/LvBr4 cells exhibited higher expression of β-catenin and increased migratory activity than parental PC14PE6 cells. Knockdown of β-catenin dramatically suppressed the motility and invasiveness of PC14PE6/LvBr4 cells, indicating β-catenin is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 40 publications
3
45
0
1
Order By: Relevance
“…USP4 has been greatly implicated in regulating tumour metastasis in breast cancer, lung cancer and colorectal cancer 19, 33, 35, 36. Notably, the loss of E‐cadherin expression accounted for USP4‐mediated augmentation of tumour metastatic capacity in all of these cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…USP4 has been greatly implicated in regulating tumour metastasis in breast cancer, lung cancer and colorectal cancer 19, 33, 35, 36. Notably, the loss of E‐cadherin expression accounted for USP4‐mediated augmentation of tumour metastatic capacity in all of these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Wnt signalling and TGF‐β signalling are 2 critical pro‐metastatic signalling pathways in various cancers with the positively regulatory impact on EMT, including melanoma 37. Several lines of evidence have revealed that USP4 was tightly associated with these 2 canonical pathways 33, 36, 38. Specifically, USP4 could directly interact with TGF‐β type I receptor (TRI) and stabilize TRI levels at the plasma membrane though its deubiquitinating activity, thereby maintaining the sustained activation of TGF‐β signalling 33.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stabilization of PRL-3 resulted in activation of Akt and reduction of E-cadherin. Besides, USP4 was also found to be highly expressed in brain metastatic lung adenocarcinoma PC14PE6/LvBr4 cell lines as a β-catenin-specific deubiquitinating enzyme, involved in the increased stability of β-catenin protein (Hwang et al, 2016). Several reports revealed that some DUBs were involved in EMT event but the identities of the substrates remain unclear.…”
Section: Dubs In Regulation Of Critical Steps In Tumor Metastasismentioning
confidence: 99%
“…86 We demonstrate here that both USP17 and USP4 are expressed at higher levels in breast and lung cancer cell lines compared to normal cells. Importantly, HAS2 was coexpressed in a similar pattern in the malignant cell lines, suggesting a correlation between HAS2, USP17 and USP4 protein levels.…”
Section: Discussionmentioning
confidence: 59%